ANALYSIS OF THE LEVEL OF DEVELOPMENT OF PHYSICAL QUALITIES IN PARA JUDO ATHLETES - Nigbayevna, Raxmatova Dilnoza (Research Focus International Scientific Journal, 2026)
This article analyzes the level of development of physical qualities in para judo athletes. The study examined key physical qualities such as strength, endurance, speed, agility and flexibility. Based on the obtained results, scientific and practical recommendations were developed to improve the training process of para judo athletes.